Β‐Zeolite‐Assisted Lignin‐First Fractionation in a Flow‐Through Reactor. Issue 18 (5th August 2021) - Kramarenko, Alexei; Etit, Deniz; Laudadio, Gabriele; D'Angelo, Fernanda Neira
Abstract: In the present work, a hydrogen‐free one‐step catalytic fractionation of woody biomass using commercial β‐zeolite as catalyst in a flow‐through reactor was carried out. Birch, spruce, and walnut shells were compared as lignocellulosic feedstocks. β‐Zeolite acted as a bifunctional catalyst, preventing lignin repolymerization due to its size‐selective properties and also cleaving β‐O‐4 lignin intralinkages while stabilizing reactive intermediates. A rate‐limiting step analysis using different reactor configurations revealed a mixed regime where the rates of both solvolytic delignification and zeolite‐catalyzed depolymerization and dehydration affected the net rate of aromatic monomer production. Oxalic acid co‐feeding was found to enhance monomer production at moderate concentrations by improving solvolysis, while it caused structural changes to the zeolite and led to lower monomer yields at higher concentrations. Zeolite stability was assessed through catalyst recycling and characterization. Main catalyst deactivation mechanisms were found to be coking and leaching, leading to widening of the pores and decrease of zeolite acidity, respectively. Abstract : Better with beta : This work addresses crucial aspects for the understanding and rational optimization of the β‐zeolite‐assisted lignin‐first fractionation: elucidation of the role β‐zeolite in the reaction network, rate‐limiting step analysis, effect of different biomass feedstocks, homogeneous acid co‐addition, and catalyst stability studies.